Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.37284/eajass.3.1.428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drug Abuse in Schools and Homes in Kenya.

Abstract: The intensity of drug abuse has been a major concern in recent years. It has invaded homes, schools, and workplaces, affecting individuals of all ages and classes (UNDCP, 1992). According to the World Drug Report 2007, approximately 200 million people, about 5% of the world’s population aged between 15 and 64 years, have used drugs at least once in the previous months. According to surveys of adolescent students in Nova Scotia in Canada, carried out in 1991 and 1996, over one-fifth (21.9%) of the students repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(5 reference statements)
0
0
0
Order By: Relevance
“…Zemba [31] found that drug abuse led to poor academic performance, absenteeism, and low concentration in class among pupils. Teresia [32] also highlights the adverse effects of drug abuse in schools, including poor academic performance. Pereira et al [33] found that implementing drug abuse prevention programs in schools was associated with the manager's experience in education and with the teaching strategies of the school.…”
Section: Introductionmentioning
confidence: 99%
“…Zemba [31] found that drug abuse led to poor academic performance, absenteeism, and low concentration in class among pupils. Teresia [32] also highlights the adverse effects of drug abuse in schools, including poor academic performance. Pereira et al [33] found that implementing drug abuse prevention programs in schools was associated with the manager's experience in education and with the teaching strategies of the school.…”
Section: Introductionmentioning
confidence: 99%